Permasalahan Guru IPS dalam Mengembangkan Bahan Ajar di Sekolah Menengah Pertama Negeri 1 IV Koto Kabupaten Agam - Rahmi, Tysa Sufia; Fatimah, Siti (Journal of Civic Education, 2023)
This study addresses the challenges faced by social studies educators in crafting materials at Junior High School Number 1 IV Koto, Agam Regency. Crafting effective teaching materials is vital for facilitating learning processes. The research employs a descriptive qualitative approach, gathering data through observations, interviews, and document analysis. Findings reveal several hurdles encountered by teachers in this context, such as difficulties in generating and implementing innovative teaching ideas, struggles with technology integration, and disparities in educational backgrounds among social science teachers. To tackle these issues, Junior High School Number 1 IV Koto has implemented various strategies, including promoting extensive reading and referencing of educational materials to broaden teachers' perspectives, providing technological training sessions, fostering collaborative initiatives among social studies teachers, and enhancing facilities and infrastructure for instructional material development. However, the study acknowledges that it does not delve into local wisdom, which could be explored by future researchers.